Oncological Patients With Endocrine Complications After Immunotherapy With Checkpoint Inhibitors Present Longer Progression-Free and Overall Survival - Paschou, Stavroula A.; Liontos, Michael; Eleftherakis-Papaiakovou, Evangelos; Stefanaki, Katerina; Markellos, Christos; Koutsoukos, Konstantinos; Zagouri, Flora; Psaltopoulou, Theodora; Dimopoulos, Meletios-Athanasios (Frontiers in Oncology, 2022)
Aim The aim of this study was to investigate the association of endocrine complications after ICI immunotherapy with progression-free survival (PFS) and overall survival (OS) in a large single-center oncological cohort. Patients and Methods In total, 351 patients were included in the analysis, 248 men (70.7%) and 103 women (29.3%). The median age was 66 years. Patients had a variety of cancer types, namely, bladder cancer (131, 37.3%), renal cancer (89, 25.4%), lung cancer (74, 21.1%), ovarian cancer (22, 6.3%), and other types of cancer (35, 10%). The majority (314, 89.4%) were classified as stage IV, while 10.6% (37) were classified as stage III. Most of the patients received immunotherapy with anti-PD1 agents (262, 74.6%) and the rest with anti-PD-L1 agents (89, 25.4%). Kaplan–Meier estimates were used to describe and visualize the effect of categorical variables on OS and PFS. Survival analysis was performed by Kaplan–Meier curves, and survival differences between groups were estimated using the log-rank test. The estimation of the prognostic value of several variables with patients’ survival was made by Cox regression models. Results In total, 68 (19.4%) of patients presented an endocrine complication after immunotherapy with ICIs. Specifically, 66 (18.8%) had thyroid dysfunction, 1 patient presented hypophysitis (0.3%), and 1 patient had a combination of thyroid dysfunction and hypophysitis (0.3%). Patients with an endocrine complication had mPFS of 15 months (95% CI 11.0–18.9 months), while in those without endocrine complication mPFS was 7 months (95% CI 6.1–7.9 months, p < 0.001). Similarly, median OS (mOS) was statistically significant lower in the patients’ group without endocrine complication. In fact, mOS was 51 months (95% CI 39.3–62.7 months) for these patients. The presence of endocrine complications after immunotherapy with ICIs retained its significance in terms of longer PFS (HR 0.57, 95% CI 0.39–0.81) and OS (HR 0.53, 95% CI 0.32–0.90) after multivariate analysis. Conclusions ICI endocrinopathies may be a positive predictor of immunotherapy response.